2015
DOI: 10.1242/jcs.174870
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic initiation factor 6 modulates myofibroblast differentiation at transforming growth factor-β1 transcription level via H2A.Z occupancy and Sp1 recruitment

Abstract: Eukaryotic initiation factor 6 (eIF6) is a pivotal regulator of ribosomal function, participating in translational control. Previously our data suggested that eIF6 acts as a key binding protein of P311 (a hypertrophic scar-related protein; also known as NREP). However, a comprehensive investigation of its functional role and the underlying mechanisms in modulation of myofibroblast (a key effector of hypertrophic scar formation) differentiation remains unclear. Here, we identified that eIF6 is a novel regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We recently reported that eukaryotic initiation factor 6 (eIF6), which is involved in ribosomal biogenesis and translational control by regulating the binding of the 40S and 60S ribosomal subunits, regulates fibrosis via the TGF-β1 pathway in animal models16, human hypertrophic scarring15, and chronic kidney disease27. eIF6 is also involved in regulating MMP-2/TIMP-2 ratios to balance the degradation and deposition of the extracellular matrix28.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported that eukaryotic initiation factor 6 (eIF6), which is involved in ribosomal biogenesis and translational control by regulating the binding of the 40S and 60S ribosomal subunits, regulates fibrosis via the TGF-β1 pathway in animal models16, human hypertrophic scarring15, and chronic kidney disease27. eIF6 is also involved in regulating MMP-2/TIMP-2 ratios to balance the degradation and deposition of the extracellular matrix28.…”
Section: Discussionmentioning
confidence: 99%
“…Because TGF-β pathway activity is intimately involved in fibrosis and collagen deposition, and eIF6 inversely modulates the expression of TGF-β1, mainly at the transcription level16, eIF6 deficiency may result in increased collagen I deposition. This prediction is supported by our results in which the level of TGF-β1 mRNA expression, as well as p-Smad protein expression, is increased in cells containing reduced levels of eIF6, suggesting the activation of TGF-β1signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations